The Students’ Perception of Speech Method toward The University Students’ Speaking Skill - Ayu Wulandari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
To perceive the existence of Speech Method toward the students’ speaking skill, this researcher conducts a descriptive qualitative research design in order to find the students’ problem that gets some difficulties. Speech Method is taught to students of the sixth semester 2014 A who learn speaking skill by delivering in front of the class with a minimally limitation of time which is given by the lecturer in order the students can speak fluently. The researcher takes 12 students who are always active in joining the Speaking IV subject as the respondents of the research. By using a questionnaire and interview as methods to collect the concrete data, the researcher concluded that the existence of Speech Method improves students’ speaking skill. It is proven in the answer of questionnaire that eleven (11) or 93% respondents agree on it. Unfortunately, there are some difficulties gotten by the students, in which many students feel nervous in delivering their speech and have limited vocabularies that make them cannot speak up in front of the audiences. While, students perceive that they just do not like on the technique used by lecturer who gives more explanation than the exercise. Mostly students also stated that the lecturer of Speech Method cannot make the class to be interesting. The students perceived that Speech Method existence improves students’ speaking skill but students want the lecturer give more exercise on having speech in order that they can learn how to speak fluently.